Between Words and Silence: Ethical challenges in researching conflicts of memory in digital era - Golonka-Czajkowska , Monika; Trebunia-Staszel, Stanisława (Culture Unbound, 2022)
This article tackles the risks of digitization of sensitive collections and the ethical limits of open access. Research into experience of conflicts and violence requires the submerging into a world of local taboos and practices that usually remain within the sphere of cultural intimacy. Similarly, the digitization of sensitive collections can grant an un-curated uncontrolled access to realms which should be handled with ethical awareness and sensitivity. We focus on two case-studies referring to the Podhale, a region in the Tatra Mountains inhabited by local people called Górale. The first one is the archive of Nazi anthropological photography and documentation recently rediscovered at the Smithsonian Institution Archives (SIA). Its digitization in 2007 marked the start of a research project on WWII anthropology in Podhale, evoking at the same time an ardent and emotional debate among both scholars and the Górale community. The most serious issues referred to the impact of the digitized photographs on the present-day collective memory of the Górale. In fact, till the archive’s discovery and digitization, the episode of Nazi racial research was literally cast out from local history and memory. In this article we will ask how to deal with such materials and conduct research among people, for whom such documentation invokes unwanted and traumatic experiences. The second case-study focuses on contemporary memory conflicts related to the anti-communist guerrilla group “B?yskawica” (Lightning) operating in the aftermath of WWII on the Polish-Slovak border in the Tatra Mountains region. Accused by communist authorities of war-crimes, these partisans were officially rehabilitated only in the aftermath of the Polish Revolution of 1989. Memories about “B?yskawica” are still very vivid in this region evoking conflicting feelings from undisputed glorification to total condemnation. This article will inquire into the ambiguous digital discourses in the social media around such conflicting memories build on digitized resources from the archives of the former secret police (now deposited at the Institute of National Remembrance; INR - Institut Pami?ci Narodowej, IPN ). Both case-studies deal with a similar period, region, type of sources (archives produced in the past by the regime’s institutions of power). Both refer to the memory of experiences of violence, difficult choices, local conflicts, oppressive regimes and practices. We argue that the transition of such sensitive data into the digital realm raises the danger of manipulation by various interest groups, arbitrary defragmentation and reconfiguration. It can enliven and even reinforce old conflicts, generate new ones and even undermine the fragile social and cultural balance within a community.